2016
DOI: 10.3382/ps/pev306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light-emitting diode (LED) vs. fluorescent (FL) lighting on laying hens in aviary hen houses: Part 2 – Egg quality, shelf-life and lipid composition

Abstract: In this 60-wk study, egg quality, egg shelf-life, egg cholesterol content, total yolk lipids, and yolk fatty acid composition of eggs produced by Dekalb white laying hens in commercial aviary houses with either light-emitting diode (LED) or fluorescent (FL) lighting were compared. All parameters were measured at 27, 40, and 60 wk of age, except for egg shelf-life, which was compared at 50 wk of age. The results showed that, compared to the FL regimen, the LED regimen resulted in higher egg weight, albumen heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
2
17
1
Order By: Relevance
“…Besides, they have a higher initial cost (Mendes et al, 2013), and they are susceptible to power fluctuations. These problems make it difficult to maintain uniform light intensity in the whole livestock production cycle (Long et al, 2015). Another drawback is that the fluorescent lamp maximum efficiency occurs when the air temperature is between 21 and 27°C.…”
Section: Types Of Lampsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, they have a higher initial cost (Mendes et al, 2013), and they are susceptible to power fluctuations. These problems make it difficult to maintain uniform light intensity in the whole livestock production cycle (Long et al, 2015). Another drawback is that the fluorescent lamp maximum efficiency occurs when the air temperature is between 21 and 27°C.…”
Section: Types Of Lampsmentioning
confidence: 99%
“…In addition, the cost of the technology has decreased significantly since its first development and it has become more accessible to the poultry industry (Long et al, 2015).…”
Section: Light Emitting Diode (Led)mentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent study revealed that a Dim-to-Blue poultry-specific LED light and a warm-white CFL led to comparable W-36 pullet performance in body weight, body weight uniformity, and mortality (Liu et al, 2017). Similarly, when applying a Nodark poultry-specific LED light (CCT = 4100K) and warm-white fluorescent lights in commercial aviary hen houses, no differences between the two types of light were detected in egg weight, egg production, feed use, mortality rate, or egg quality parameters for DeKalb white hens (Long et al, 2016a(Long et al, , 2016b. In addition, a study found that the effects of LED lights on broiler growth were age-related (Yang et al, 2016).…”
mentioning
confidence: 93%
“…However, there are few studies on the effects of LED light on layers reared in alternative rearing systems [9,14]. Moreover, there is little information about the effect of LED and fluorescent lighting on production performance, egg quality, stress, and fear in hens [9,14,15]. Additionally, different light intensity levels were reported on different levels of the cage tiers, and this may affect the welfare parameters in layers [13].…”
Section: Introductionmentioning
confidence: 99%